Hybrid structure of u bent optical fiber local surface plasmon resonance sensor based on graphene - Saffana Zeiab Maseer; Bushra Razooky Mahdi; Nahla Abd Aljbar (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this paper, a fiber optic sensor was designed and implemented to detect the change in refractive index of sodium chloride salt solution based on the local surface plasmon resonance (LSPR) phenomenon. This sensor was manufactured using a plastic optical fiber (POF), this optical fiber was bent in a U-shape with 0.5cm bending diameter, and then the cladding and part from core of the fiber were removed by polishing at the sensor head to become as a D-shape in cross section. The sensor was coated with 30 nm thickness of gold nano particles (GNPs) by DC plasms coating technology and it was tested with sodium chloride solution, the detection sensitivity was 466.66 nm/RIU. To enhancement the sensitivity, the latest sensor was coated with 20nm thickness of graphene nano material and retested with same samples of sodium chloride solutions. It was found that graphene improved the sensitivity by an excellent amount, where shift in wavelength was 20nm and highest sensitivity obtained was 666.666 nm/RIU.